2017
DOI: 10.1111/ajco.12768
|View full text |Cite
|
Sign up to set email alerts
|

Image‐guided IMRT with simultaneous integrated boost as per RTOG 0529 for the treatment of anal cancer

Abstract: Simultaneous integrated boost IMRT and concurrent chemotherapy as per RTOG 0529 protocol seems to be safe and feasible with consistent oncological outcomes and a mild acute and late toxicity profile in anal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
7
23
0
1
Order By: Relevance
“…Franco et al (2016) showed comparable rates of acute toxicity in a retrospective analysis of 39 patients treated with VMAT and simultaneous integrated boost (SIB). The same team published later data about the efficacy of this schedule in the same population: their data showed encouraging LC, DFS and OS rates (Arcadipane et al 2017). These data have been confirmed by Mitra et al (2017) in a larger, long-term experience on 99 patients treated with VMAT-SIB delivered with the schedule of the RTOG 0529 trial: at a median follow-up of 49 months (range 2-114 months), the 4-year overall survival was 85.8%, and 4-year event-free survival was 75.5%.…”
Section: Discussionmentioning
confidence: 96%
“…Franco et al (2016) showed comparable rates of acute toxicity in a retrospective analysis of 39 patients treated with VMAT and simultaneous integrated boost (SIB). The same team published later data about the efficacy of this schedule in the same population: their data showed encouraging LC, DFS and OS rates (Arcadipane et al 2017). These data have been confirmed by Mitra et al (2017) in a larger, long-term experience on 99 patients treated with VMAT-SIB delivered with the schedule of the RTOG 0529 trial: at a median follow-up of 49 months (range 2-114 months), the 4-year overall survival was 85.8%, and 4-year event-free survival was 75.5%.…”
Section: Discussionmentioning
confidence: 96%
“…[9][10][11] Comparison to other smaller IMRT series is difficult owing to the varying outcome definitions; however, 2-year, 3-year, and 4-year DFS is reported as 84.4%, 71%, and 82% in smaller published series. [28][29][30][31] In terms of patterns of relapse we can compare to the 4 retrospective cohorts of a 3D conformal technique, acknowledging that these publications reported different outcomes and definitions of outcomes. [32][33][34][35] Our LRR (19.5%) is similar to the 14.4% to 25% presented in these papers.…”
Section: Discussionmentioning
confidence: 99%
“…Also RT, as a mainstay treatment option in the multimodality management of cancer, needs quality assurance (QA) protocols to constantly check for the quality of treatments (target volume delineation, treatment plan optimization, dosimetric results and delivery reliability) [11] . The contouring process of the target volume is a major source of uncertainty and error in RT and, since, most of the times, this potential error remains constant during the whole RT treatment, it may have a detectable impact on the dose received by the tumor, especially for highly conformal techniques, such as volumetric modulated arc therapy (VMAT) and whenever image-guidance (with consequent CTV to PTV margin reduction) is employed [18] , [19] , [20] . The factors that most consistently influence target delineation variability include gross disease visibility, disagreement on target definition, extension and interpretation or lack of dedicated contouring protocols [18] , [21] .…”
Section: Discussionmentioning
confidence: 99%